Comparison between Xia and Walfisch-Ikegami models for low-rise building path loss prediction - Supachai Phaiboon (2018)
This paper presents path loss prediction on 2-D aerial images taken from the actual areas. The original Xia path loss model and the Walfisch-Ikegami model were applied for predicting in low rise building area. In case of the Xia model for non line of sight (NLOS), it requires a set of model parameters such as distance from the last roof top to receiver, average building height, and antenna heights. While the Walfisch-Ikegami (WI) model requires road parameters such as road width and road orientation. We performed measurements at frequencies of 900 and 1800 MHz for comparison between the two approaches. From the results it is found that the Xia model provides good agreement, while the WI model provides good agreement especially when the receiver is on the street between two buildings. © 2010 IEEE.